Pelatihan dan Pameran Desain Poster Daring untuk Remaja Indonesia - Maulina, Rini; Cahyadi, Arif Try; Madjid, Wahyu Maulana; Dewi, Febby Permata (Universitas Komputer Indonesia, 2020)
Community Service (PKM) have been conducted by Lecturers and students from the Visual Communication Design Study Program, Faculty of Design, Universitas Komputer Indonesia (UNIKOM). PKM is implemented on the basis of the needs of partners, namely SMK Nasional Bandung towards the advancement of creativity, achievement and confidence of its students through competition. PKM program, namely COVID-19-themed Poster Design Training that is agreed can be attended by participants from all over Indonesia. 124 participants, conducted online. The purpose of PKM activities to increase creativity, achievement, and confidence of SMK Nasional Bandung students. The PKM method consists of the implementation method and the method of analysis of the work. The method of implementation of PKM consists of 13 stages, including need assessment, introduction, training, workshop, curation, exhibition, and awards. The visual analysis method argued was used to test the results of the training on 3 works of the best participants. As a result of the poster design training there are 52 poster design works on display on the https://ideas.my.id. the results of the visual argument analysis show trainees understand the training materials.